2010
DOI: 10.1057/rpm.2009.54
|View full text |Cite
|
Sign up to set email alerts
|

Revenue impacts of demand unconstraining and accounting for dependency

Abstract: Accurate forecasts are crucial to an airline revenue management system. Historical demand data for two fare classes used for forecasting in an airline are often censored and correlated. In this article, we propose a methodology that takes into account both censorship and correlation of demands. We then study its impact on the expected revenue and compare it with three standard methodologies available in the literature by using extensive simulation. Our results show that the opportunity cost of neglecting deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In the early 2010s, Karmarkar et al (2011) looked at two fare classes, and included correlation of demand between the classes when estimating the uncensored demand and found the improved demand estimates generated simulated revenue increases of 1-2 per cent. Guo et al (2011) derived formulas for EM and PD when nominal demand is assumed to follow distributions such as Gamma, Weibull, Exponential and Poisson.…”
Section: General Surveys and Simulationsmentioning
confidence: 99%
“…In the early 2010s, Karmarkar et al (2011) looked at two fare classes, and included correlation of demand between the classes when estimating the uncensored demand and found the improved demand estimates generated simulated revenue increases of 1-2 per cent. Guo et al (2011) derived formulas for EM and PD when nominal demand is assumed to follow distributions such as Gamma, Weibull, Exponential and Poisson.…”
Section: General Surveys and Simulationsmentioning
confidence: 99%
“…Empirical studies show that an amount between 45% and 84% of demand can be substituted [5,6]. In [7], it is showed that the cost of ignoring demand dependency is 1% higher than ignoring censorship. To illustrate this problem, suppose that an online library offers 2 types of books for each ISBN: 1-new book, 2-used books and their quantities are 30 for new books and 15 for used books.…”
Section: Introductionmentioning
confidence: 99%